Developing an electrochemical sensor for the in vivo measurements of dopamine - Delmo Naela; Mostafiz Bahar; Ross Ashley E.; Suni Johanna; Peltola Emilia (Royal Society of Chemistry, 2025)
Measurements inside the human body are complicated. Here, we provide a short introduction of the main requirements for the successful in vivo determination of dopamine concentrations, together with a discussion of how the type of the measurements, short-term vs. long-term and dynamic vs. basal measurements, affects what is expected from the sensor material. Next, we provide a step-by-step guide for characterising electrode performance and performing in vivo measurements with practical tips. Finally, we discuss the typical approaches for overcoming the challenges set by the environment.